Effect of citronellol and the Chinese medical herb complex on cellular immunity of cancer patients receiving chemotherapy/radiotherapy - Zhuang, Shu-Ru; Chen, Su-Lin; Tsai, Jih-Hsin; Huang, Chi-Chou; Wu, Tzu-Chin; Liu, Wen-Shan; Tseng, Hsien-Chun; Lee, Hong-Sen; Huang, Min-Chang; Shane, Guang-Tzuu; Yang, Cheng-Hua; Shen, You-Cheng; et al. (Phytotherapy research, 2009)
Leukopenia and immunity impairment usually occur during cancer therapy. Citronellol, an oil soluble compound derived from the geranium, has anticancer and antiinflammatory properties, as well as promoting wound healing. Ganoderma lucidum, Codonopsis pilosula and Angelicae sinensis are traditional Chinese herbs, all of which have proven immunomodulatory functions in laboratory-based research. This randomized, double-blind, placebo-controlled study examined whether the Chinese medicinal herb complex (CCMH; a mixture of citronellol and extracts of G. lucidum, C. pilosula and A. sinensis) improves the immune cell counts of cancer patients receiving chemotherapy and/or radiotherapy. A total of 105 cancer patients receiving chemotherapy or radiotherapy were enrolled. The quantities of immune cells in the blood of the subjects were determined before and after 6 weeks of cancer treatment, with either CCMH or a placebo. CCMH significantly reduced the depletion of leukocytes (14.2% compared with 28.2%) and neutrophils (11.0% compared with 29.1%). Analysis of the lymphocyte phenotype revealed that the patients receiving the placebo had reduced CD4 lymphocytes and natural killer (NK) cells than the CCMH-treated patients. Treatment with CCMH for patients receiving chemotherapy and/or radiotherapy may improve their immune function, improving their ability to fight off the cancer, as well as any secondary infections that could compromise their treatment and their health. Copyright © 2009 John Wiley & Sons, Ltd.